Treatment of Essential Tremor: Are there Issues We are Overlooking? - Louis, Elan D. (Frontiers in Neurology, 2012)
Background: Essential tremor (ET) is one of the most common neurological diseases. Although a large number of medications have been tested, there are only two first-line medications, primidone and propranolol, which is a situation that has not changed in approximately 30 years. Several recent reviews have summarized the current pharmacotherapeutic options for ET and the approach to the management of ET patients. Yet there remain a number of important issues, both scientific and clinical, that have not been broached in the literature and that have therapeutic implications. Objectives: To introduce several clinical and scientific issues that have not formally entered the published literature on the treatment of ET. Methods: In September 2011, materials for this article were gathered during a literature search of PubMed using the following terms: essential tremor, clinical, clinical trial, treatment, medications, therapeutics. English-language articles were selected for further review. Results: The paper focuses on several topics that have received scant or no discussion in the published literature on ET therapeutics. These topics are as follows: the nature of the underlying disease pathophysiology, the presence of pathological heterogeneity, the complexity of cellular and neurochemical changes which may be underlying this disorder, the presence of clinical heterogeneity, the selection of treatment endpoints, the effects of diagnostic uncertainty, the presence of cognitive and psychiatric features in ET, the identification of possible modifiable risk factors and the absence of any neuroprotective therapies. Conclusions: The author has identified several topics that have received scant or no discussion in the published literature on ET therapeutics. Further discussion of the issues raised here may lead to improvements in clinical trial methodologies as well as facilitate the development of fresh approaches to pharmacotherapy.